Mediating role of emotion in personalised relationship formation: study of patient-physician relationship. (1st January 2014) - Kumar, Praveen; Arora, Ashok Pratap; Gupta, Rajen
The paper tests a comprehensive model that explains relative influence of 'professional service provider behaviour' and 'customer emotions' on 'relationship', 'satisfaction', and its subsequent influence on 'post purchase behaviour' in the high contact, high credence extended service situations. One-on-one interviews with 256 patients were used to construct and validate relationships using the structural equation model. The results suggest that customers' positive appraisal of essential service provider behaviour results in customer satisfaction and re-patronisation intention. Customers' perception of relationship with the service provider which is consequent of service providers' interpersonal behaviour and customer experience of positive emotions in service interaction result in customer advocacy.